Cardiac MRI in Suspected Acute Myocarditis After COVID-19 mRNA Vaccination - Kravchenko, Dmitrij; Isaak, Alexander; Mesropyan, Narine; Endler, Christoph; Bischoff, Leon; Vollbrecht, Thomas; Pieper, Claus Christian; Sedaghat, Alexander; Kuetting, Daniel; Hart, Christopher; Feisst, Andreas; Attenberger, Ulrike; Luetkens, Julian Alexander (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
Purpose To evaluate cardiac MRI characteristics in patients with suspected hypersensitivity myocarditis following mRNA COVID-19 vaccination.Materials and Methods Patients clinically suspected of acute myocarditis after COVID-19 vaccination were retrospectively analyzed and compared against a healthy control group. Cardiac MRI protocol included parameters such as T1 and T2 relaxation times, extracellular volume (ECV), T2 signal intensity ratio, and late gadolinium enhancement (LGE). Lymph node size was assessed in the patient group on the injection side. Student t-test, analyses of variance (ANOVA) with Tukey post-hoc test, and χ2 test were used for statistical analysis.Results 20 patients with clinically suspected post-vaccine myocarditis (28 ± 12 years; 12 men) and 40 controls (31 ± 11 years; 25 men) were evaluated. According to the 2018 Lake Louise criteria (LLC), patients with clinically suspected myocarditis were further subdivided into an LLC-positive group (n = 9) and an LLC-negative group (n = 11). The mean time of symptom onset after vaccination was 1.1 ± 1.2 days (LLC-positive) and 6.5 ± 9.2 days (LLC-negative). Group differences in inflammatory variables between myocarditis patients and control subjects were more pronounced in the LLC-positive group (e. g., T1 relaxation time: 1041 ± 61 ms [LLC positive] vs. 1008 ± 79 ms [LLC-negative] vs. 970 ± 25 ms [control]; p <.001; or T2 signal intensity ratio 2.0 ± 0.3 vs. 1.6 ± 0.3 [LLC-negative] and vs. 1.6 ± 0.3 [control], p = .012). LLC-positive patients were significantly faster in receiving an MRI after initial symptom onset (8.8 ± 6.1 days vs. 52.7 ± 33.4 days; p = .001) and had higher troponin T levels (3938 ± 5850 ng/l vs. 9 ± 11 ng/l; p <.001). LGE lesions were predominantly located at the subepicardium of the lateral wall. Axillary lymphadenopathy was more frequent in the LLC-positive group compared to the LLC-negative group (8/9 [89 %] vs. 0/11 [0 %], p < 0.001).Conclusion Vaccine-induced myocarditis should be considered in patients with acute symptom onset after mRNA vaccination, especially if elevated serum troponin T is observed. Imaging findings of vaccine-induced myocarditis are similar to virus-induced myocarditis, allowing for the use of the Lake Louise Criteria for diagnostic purposes.Key Points: Citation Format
Keywords: vaccine; myocarditis; cardiac MRI; COVID-19